The development of a theory-based eHealth app prototype to promote oral health during prenatal care visits. Issue 6 (22nd April 2019) - Vamos, Cheryl A; Griner, Stacey B; Kirchharr, Claire; Green, Shana M; DeBate, Rita; Daley, Ellen M; Quinonez, Rocio B; Boggess, Kim A; Jacobs, Tom; Christiansen, Steve
Abstract : Nurse practitioners and midwives reported that an eHealth app prototype assisted in providing them with the information, motivation, and skills needed to implement the oral health guidelines into routine prenatal care visits. Abstract: Poor maternal oral health during pregnancy is associated with adverse maternal and child outcomes, including preterm birth and early childhood caries. Subsequently, professional associations have developed prenatal oral health guidelines, but significant gaps exist in implementing guidelines into clinical practice. The purpose of this study was to develop and test the usability of an innovative, theory-driven, eHealth application ("app") to facilitate prenatal providers' (nurse practitioners and midwives) implementation of oral health promotion during prenatal care visits. App development was guided by previous research, an integrated conceptual framework, Scientific Advisory Board input, and consumer-engaged iterative processes utilizing mixed-methods (observations, surveys, in-depth interviews) among providers ( n = 4) during 10 unique prenatal care visits at a federally qualified health care center. Triangulation of quantitative and qualitative data analysis produced descriptive frequencies and salient themes. Concepts and principles from the following theoretical frameworks informed intervention development and testing: Consolidated Framework for Implementation Research ; Information–Motivation–Behavioral Skills Model ; Health Literacy ; and Brief Motivational Interviewing . Overall, providers reported the app was effective at providing the information, motivation, and behavioral skills needed to integrate oral health promotion (e.g., easy to use; provided cues to action via scripts and tailored education; and documented findings into the patient's record). Although providers reported high usability, time constraints and detailed patient counseling scripts were identified areas for improvement. Findings suggest that the eHealth app could serve as an innovative mechanism to assist providers in implementing the prenatal oral health guidelines into practice. Future research is needed to continue app development efforts and to determine efficacy and effectiveness in practice settings.